Implementation of Indonesia's Sea Defense Strategy Policy In Facing Military Threats to Support Sea Power - Puja Sari Putri; Ansori Ansori; Reghina R. Syifaranie S.; Anis Nurlaily; Hafidz K. Jati (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
Indonesia in realizing the World Maritime Axis country requires good physical and mental conditions where all elements greatly affect the performance and performance of the country in carrying out defense and security in order to achieve national goals. This article uses a qualitative method. Regarding the Implementation of the Archipelago Sea Defense Strategy Policy in Facing Military Threats to Support Sea Power. Using the theory of policy implementation according to Edward III, namely Communication, Resources, Disposition and Bureaucratic Structure. To obtain data using the Library Research method, which includes the use of books, scientific journals, trade publications, magazines, newspapers, the internet, and artifacts. That when viewed based on Edward III's first policy implementation theory of communication that good communication will bring Indonesia into defense diplomatically with the country concerned without having to go to war, disposition requires Indonesia to take an active role in collective security efforts in the ASEAN Regional region so as to create decisions that can be mutually agreed upon in cases of territorial waters or state borders in the ASEAN Regional region, resources require Indonesia to understand the current threat spectrum that the glass of power of great power countries has occurred in the region so that the government must take the right steps in fulfilling both human resources and defense equipment, and finally the bureaucratic structure where all elements responsible for marine security must take part in maintaining marine security and defense and minimizing the egocentricity of each institution in order to achieve national goals